POTRET PEMBELAJARAN KONVENSIONAL DI ERA KURIKULUM MERDEKA: STUDI OBSERVASI DI SDN 1 TELAGA BIRU - Fandi H. Binggo; Fitri Adelia Nur Mahmud (Jurnal Ilmu Pendidikan UMGo, 2025)
This article describes the portrait of conventional learning practices during the implementation of the Merdeka Curriculum at SDN 1 Telaga Biru. The study was conducted through a qualitative descriptive approach using direct classroom observation, field notes, and simple documentation during the School Field Introduction Program (PLP 1). The findings indicate that learning activities are still dominated by textbooks, teacher explanations, and question-answer routines, while the use of alternative media and digital technology remains limited. This condition reflects a gap between the principles of the Merdeka Curriculum, which emphasize student-centered, differentiated, contextual, creative, and technology-supported learning, and classroom practices that remain teacher-centered. Several factors contribute to this situation, including limited practical training, uneven digital competence, teacher dependence on familiar routines, and the lack of continuous mentoring at the school level. The study concludes that curriculum transformation requires not only policy documents but also sustained teacher professional development, instructional leadership, collaborative reflection, and adequate learning resources. These findings are expected to serve as an initial reflection for prospective teachers, schools, and stakeholders in strengthening innovative and contextual learning in elementary education.